FRI0101 Unmet needs in the treatment of rheumatoid arthritis. an observational study and a real-life experience from a single university centre. (12th June 2018) - Kaltsonoudis, E.; Pelechas, E.; Voulgari, P.V.; Drosos, A.A.
Abstract : Background: Despite the progress in the treatment of rheumatoid arthritis (RA), a significant number of patients does not achieve low disease activity (LDA). Objectives: The purpose of this study was to estimate the size of unmet needs in the treatment of RA, using all the conventional synthetic disease modifying antirheumatic drugs (csDMARDs) and/or biological DMARDs (bDMARDs) in a long-term observational study. Methods: Between January 2006 and December 2017, 538 patients with early RA were followed up in the outpatient rheumatology clinic. All patients fulfilled the 2010 ACR/EULAR classification criteria, had disease duration less than 1 year and were csDMARDs and bDMARDs naive. The patients were treated according to EULAR and ACR recommendations and strategies for RA. The following csDMARDs were introduced: methotrexate (MTX), leflunomide (LFN), sulfasalazine (SSZ) and hydroxychloroquine (HCQ). In addition, the following bDMARDs were used: abatacept, adalimumab (ADA), certolizumab, etarnecept (ETN), golimumab, infliximab (INF), rituximab and tocilizumab. Finally, small doses of steroids were used. During follow-up the clinical, laboratory findings as well as the treatment decisions and strategies were all recorded. In addition, the adverse drug reactions, the reason of termination or changing strategies, disease complications and comorbidities were all recorded. Finally, disease activity was measured with the 28 joint count, Disease Activity score-28 (DAS-28) using the erythrocyte sedimentation rate. Results: All patients have received one csDMARD, at least for 6 months. The csDMARD of first choice was MTX (58%), followed by LFN (32%), HCQ (8%), and SSZ (2%) with or without small doses of steroids. The bDMARD of first choice was INF (37%) followed by ETN (32%) and ADA (31%). During the follow up period, 14 patients were lost. In addition, 7 patients never received bDMARDs due to various comorbidities. Thus, the final results are referred to 517 patients. Among those patients, 324 (66%) were treated with csDMARDs as monotherapy or in combination therapy with or without the use of steroids with significant clinical improvement and sustained LDA. However, eleven patients (3, 2%) from this group neither achieved LDA, nor received bDMARDs, due to comorbidities. On the other hand, 175 patients (34%) were treated with bDMARDs with or without csDMARDs or/and steroids. The majority of them demonstrated sustained LDA for a long period of time. From this group 31 patients (17, 7%) never achieved LDA, despite that they switched and received all bDMARDs. Thus a total of 20, 9% of our patients never achieved LDA. Conclusions: Using the EULAR and ACR recommendations for RA therapy we successfully treated the majority of our patients. However, we found that the size of gap and the unmet needs for RA treatment is about twenty per cent. This is the first study aiming to estimate the gap and the size of unmet needs for RA treatment in a large patient population followed-up in a tertiary university centre. Disclosure of Interest: None declared